Model design of a compact delayed gamma-ray moderator system using 252Cf for safeguards verification measurements. (June 2019) - Rodriguez, Douglas C.; Rossi, Fabiana; Takahashi, Tohn; Seya, Michio; Koizumi, Mitsuo
Abstract: Delayed gamma-ray spectroscopy (DGS) is an active-interrogation nondestructive assay technique that can be used to determine the composition of a nuclear material sample by comparing the ratios of fission product gamma-ray peak intensities. However, high-radioactivity nuclear material (HRNM) contains long-lived fission products that can overwhelm a detector and shielding must be used to reduce the count rate, while minimally affecting those gamma rays from short-lived fission products with energy above 3-MeV. To compensate for the signal loss through the shielding, low-energy neutrons are required to induce more fission events from the high thermal cross-section of fissile nuclides. To improve practical safeguards DGS capabilities, we are developing a compact interrogation system to moderate ∼ 2-MeV neutrons that are easier to moderate than 14-MeV neutrons from standard deuterium-tritium generators. This work describes the optimization of an ideal moderator system for a 252 Cf neutron point source that results in a neutron fluence of 25.9 × 10 − 4 cm −2 n source − 1 passing through the sample space with ≳ 70% of those below 1-eV. Modifications for practical fabrication resulted in ⩽ 20 % reductions of the flux compared to the optimized ideal design. Finally, evaluations made of HRNM DGS signals and backgrounds conclude that a 252 Cf source intensity of 8.9 × 10 7 neutrons per second is required for a single-pass interrogation within this ideal moderator system. However, this can be as low as 3.6 × 10 6 neutrons per second using smaller samples that require less shielding. Abstract : Highlights: Moderator optimized to increase the flux by a factor of 20–30 in the sample space. Direct 70 to > 100 % of the source neutrons into the sample space. Increase the thermal-to-fast neutron ratio by a factor of > 1000 . 20% reductions resulting from practical modifications for fabrication potential. Need ⩽ 6 % of the source neutrons compared to a DT generator under similar conditions.